Gingival Recession Post Periodontal Treatment in Diabetic Patients with or without Topical Antibiotics - Choudhary, Aeman; Rana, Shazana; Gul, Ambreen; Zakria, Naila; Javed, Wajeeha; Fatima , Urooj (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the recession following Scaling and Root Planning (SRP), and to compare the efficacy of Metronidazole (MTZ), Minocycline (MC) gels, and their combination in terms of recession for the management of diabetic periodontitis patients. Study Design: Randomized Single Blind Clinical Study. (clinicaltrials.gov: NCT06027151) Place and Duration of the Study: Pharmacology, Biochemistry, and Periodontology Department, Dental College, HITEC-IMS HIT Taxila Cantt, Pakistan, from Sep 22 to Aug 23. Methodology: In this clinical study, 380 diabetic chronic periodontitis patients were randomly grouped into 4 categories: scaling and root planing (SRP) alone (Group-I), SRP plus Metronidazole Gel (Group-II), SRP plus Minocycline Gel (Group-III), and SRP plus both Metronidazole and Minocycline Gels (Group-IV). The effectiveness of four treatment regimens was assessed by checking the difference in periodontal measurements, i.e., recession at baseline, after 15 days, and 45 days of the treatment, and the percentage was measured. Results: There was a notable reduction in recession after the treatment. The overall efficacy was most pronounced in Group-IV patients managed with the combination regimen, demonstrating an Improvement rate of 19%. Groups I, II, and III achieved similar efficacy rates of approximately 3.12%, 4.21%, and 4.40% respectively. Conclusion: Metronidazole gel has similar effectiveness to Minocycline gel, and their combination has exhibited synergistic effects in treating diabetic periodontitis patients and should be used as an adjunct to SRP for enhanced clinical outcomes.